A new species of Indo-Pacific Modulidae (Mollusca: Caenogastropoda) - Lozouet, Pierre; Krygelmans, Anouchka (Zootaxa, 2016)
Modulidae is a littoral cerithioid family exclusively encountered in tropical and subtropical regions. It contains 12 to 15 living species (some species are not clearly delimited). Only one species is known to occur in the vast Indo-Pacific region (Bouchet 2015) and two species in the eastern Atlantic. By comparison, the tropical American regions are relatively rich with at least eleven living species (two or three species in the eastern Pacific and nine or more in the western Atlantic), and an equivalent number or more of fossil species (Landau et al. 2014).